Daya Dorong Pertumbuhan Ekonomi terhadap Pemerataan Kesejahteraan Sosial - Hasanah, Hasanah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the impact of economic growth on equity and social welfare across the five provinces of Kalimantan. The research focuses on examining the relationship between economic growth and three socio-economic indicators: income disparity, poverty level, and unemployment rate. A quantitative approach is employed using annual panel data from 2018 to 2024, analyzed through the Fixed Effect regression model. The results reveal that economic growth has a negative and significant effect on income disparity and unemployment, but no significant effect on poverty levels. These findings indicate that while economic growth contributes to reducing inequality and expanding employment opportunities, it has yet to substantially benefit impoverished populations. Therefore, more inclusive and equitable development strategies are needed to ensure that the benefits of economic growth are broadly distributed among all segments of society.